Linguistic and Auditory Assessment: An Effort to Improve the Beginning Reading Ability of Dyslexic Children in Grade IV at Elementary School Level - Aprilia, Imas Diana; Syafril, Muthia; Susetyo, Budi (Angstrom Centre of Education, 2024)
This study describes the implementation of linguistic and auditory awareness assessment in improving dyslexic children's early reading skills. The factors studied include linguistic (phoneme, morphology, orthography) and auditory (phoneme, morpheme, semantic, syntax) awareness, which are important in the early reading process. The research method was descriptive qualitative, with one 10-year-old student subject from grade 4. The assessment phase involved classical identification with learning instruments from grade 4 to grade 1, as well as a pre-early reading assessment focusing on linguistic and auditory awareness. Results showed significant linguistic awareness (33.59%) and auditory awareness (60%) influence reading ability. Phoneme and morphology aspects affect reading ability in terms of linguistics, while morphemes and syntax are significant in auditoris.